초고화질 VR 음악 공연영상 만족 및 이용의도에 영향을 미치는 요인에 관한 연구 - 조훈(Hoon Cho); 한경석(Kyeong-Seok Han); 안용준(Yong-Jun An ); 홍수희(Su-Hee Hong) (디지털콘텐츠학회논문지, 2020)
최근 VR 기술을 활용한 다양한 서비스들이 등장하고 있으며, VR을 활용하여 음악 공연영상을 제공하는 서비스가 주목받고 있다. 따라서 현재 초고화질 VR 음악 공연영상을 사용하는 사용자들의 만족도를 알아보는 것은 중요한 연구 주제라고 판단된다. 본 연구는 VR을 활용한 초고화질 VR음악 공연영상 만족 및 이용의도 영향을 미치는 요인에 대해 파악해 보고자 하였다. 이를 위해 VR 음악 공연영상 콘텐츠 요인을 선정하고, VR 특성 요인 그리고 이러한 특성들에 대해 사용자들의 만족도를 파악해보고자 기대일치이론을 중심으로 연구모형을 구성하였다. 이러한 연구 모형과 연구 가설을 검증하기 위하여 VR 음악 공연영상을 사용한 사용자 대상으로 실증 조사를 진행했다. 이를 통해 초고화질 VR 음악 공연영상에 대한 사용자들의 만족 및 이용의도에 대한 실증적 연구를 진행하였다. Recently, various services utilizing VR technology have emerged, and services providing music performance videos using VR are attracting attention. Therefore, it is considered an important research subject to find out the satisfaction level of users who use the ultra high definition VR music performance video. The purpose of this study was to investigate the factors affecting satisfaction and usage intention of ultra high definition VR music performance video using VR. For this purpose, the research model was constructed based on the expectation agreement theory to select VR music performance video content factors and to grasp the VR characteristic factors and users' satisfaction with these characteristics. In order to verify the research model and research hypothesis, the empirical research was conducted for the users who used VR music performance video. Through this, we conducted an empirical study on users' satisfaction and intention to use the ultra high definition VR music performance video. KCI Citation Count: 11